Mechanical properties of copper ferrite cufe2o4-polymer composite fabricated using 3d printer - Lee, Chye Heng (School of Material Engineering, University Malaysia Perlis, 2016)
The effect of speed of powder dispenser on the mechanical properties of ABS-CuFe2O4 composites was studied. The samples in the experiment were printed by 3D printer which produce three dimensional objects from the digital file are built up layer by layer. The amount of filler content added into each sample was controlled by the speed of powder dispenser which is off, low, medium, and high. The properties of pure ABS and composite ABS CuFe2O4 samples were investigated based on the distribution of fillers. Weight percentage (wt. %) of filler added into each sample was determined by using thermogravimetric analysis (TGA) and the density of the composites were identified by using density test. Tensile test and Vickers microhardness were carried out to determine the effect of filler content on mechanical properties. The effect of filler on viscoelastic behavior was assessed by using dynamic mechanical analysis (DMA). Addition of filler content in ABS matrix slightly decreases the strength of composite from 17.1MPa to 14.64MPa. Besides, storage and loss modulus were decreases with the speed of powder dispenser. The agglomeration of filler particle at high loading causes formation of microvoids that lowering both mechanical and viscoelasticity of composite can be seen on the surface morphology of the fracture surface with scanning electron microscope (SEM).